The Optimal Capital Structure Analysis of PT Lion Metal Works Tbk Listed on the Indonesia Stock Exchange - Sopian, Muh. Fauzan Anfasa; Abduh, Ardiansyah; Baso, Nurfatimah Azzahra; Mustafa, Riad (Entrepreneurship, Management, and Business Research Journal, 2025)
This study aims to determine and analyze the Optimal Capital Structure at PT Lion Metal Works Tbk, which is listed on the Indonesia Stock Exchange in 2018-2022. The variables in this study are capital structure (independent variables) measured by calculating the Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Long Term Debt to Equity Ratio (LDTER), and Return on Equity (ROE) using units of Rupiah (Rp). Data collection using the documentation method. The data analysis technique used in this research is quantitative analysis of secondary data. The results of this study indicate that the average amount of DAR is 32.31% of the industry standard <35% with optimal information, the average amount of DER is 47.83% of the industry standard <90% with optimal information, the amount of LDTER is 20.37% with industry standards <10% with non-optimal information, and the amount of ROE is 0.013% of the industry standard 40% with non-optimal notification.